2008
DOI: 10.1063/1.2835439
|View full text |Cite
|
Sign up to set email alerts
|

High-β, improved confinement reversed-field pinch plasmas at high density

Abstract: In Madison Symmetric Torus [Dexter et al., Fusion Technol. 19, 131 (1991)] discharges where improved confinement is brought about by modification of the current profile, pellet injection has quadrupled the density, reaching ne=4×1019m−3. Without pellet injection, the achievable density in improved confinement discharges had been limited by edge-resonant tearing instability. With pellet injection, the total beta has been increased to 26%, and the energy confinement time is comparable to that at low density. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…Research on Reversed Field Pinch (RFP) configurations has experienced in the recent years substantial progress [Marrelli 2007, Wyman 2008, Brunsell 2006, Hirano 2006, with significant advances both in terms of plasma performance and control, and of understanding of relevant physics. The aim of this paper is to add to the line of such progress new interesting physics results, which are emerging from the reliable operation of RFX-mod in the regime with plasma current above 1 MA.…”
Section: Introductionmentioning
confidence: 99%
“…Research on Reversed Field Pinch (RFP) configurations has experienced in the recent years substantial progress [Marrelli 2007, Wyman 2008, Brunsell 2006, Hirano 2006, with significant advances both in terms of plasma performance and control, and of understanding of relevant physics. The aim of this paper is to add to the line of such progress new interesting physics results, which are emerging from the reliable operation of RFX-mod in the regime with plasma current above 1 MA.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in MST succeeded in achieving a maximum β p of 40% by using PPCD in combination with a pellet injection technique, with an energy confinement time of ∼ 5 ms; this represents a five-fold improvement in confinement compared to the standard case [11]. It can be estimated that electrons contributed about half of the β p .…”
mentioning
confidence: 99%
“…Single helicity (SH) or quasisingle helicity (QSH) states are believed to provide a better confinement with respect to turbulent RFP configurations. Experimental studies have shown the improvement in confinement associated with the presence of QSH states [6][7][8].…”
mentioning
confidence: 99%